Comparing Deemed and State Universities on Perception of Educational Offerings Using Factorial MANOVA - Singh, Archana; Kazi, Roshan; Divekar, Rajiv; Patankar, Anita (Prabandhan: Indian Journal of Management, 2020)
Purpose: The study intended to offer evidence for three propositions: whether deemed and state universities differ in their educational offerings; whether the worth of educational offerings depends on the appropriateness of fee perception by students; and whether the relationship between the "perception of fee appropriateness" and "education offerings" is dependent on the type of university. Design: Experimental design was adopted to address the research concern - "appropriateness of fee charged will stimulate value proposition in management education." We used factorial MANOVA to explore three effects (Main Effect 1: it is hypothesized that deemed and state universities differ in their educational offerings; Main Effect 2: Worth of educational offerings depends on the appropriateness of fee perception by students; Interaction Effect: Relationship between "perception of fee appropriateness" and "education offerings" is dependent on the type of university [interaction effect is not zero]). Findings: The results of factorial MANOVA revealed a major finding that if students feel they are charged appropriately, they will rate educational offerings, academic excellence, infrastructure, career aspirations, and skills acquired, as superior. Research Limitations: The study did not include management students of private universities and autonomous colleges. The study was cross-sectional in time dimension and not longitudinal, and hence, a causal relationship could not be established. Originality/Value: It is the first study to use factorial MANOVA to test two main effects and one interaction effect with respect to educational offerings of deemed and state universities.